Erythema dyschromicum perstans (ashy dermatosis) - case reports - Lange, Magdalena; Trzeciak, Magdalena; Sokołowska-Wojdyło, Małgorzata; Roszkiewicz, Jadwiga (Dermatology Review/Przegląd Dermatologiczny, 2011)
Introduction . Erythema dyschromicum perstans (EDP) is an acquired disease, rare in the Caucasian race, with characteristic greyish, ashy-coloured skin lesions. The aetiology of the disease is unknown. Objective. To present 5 patients with EDP in relation to cases described in the literature as: ashy dermatosis, lichen planus pigmentosus , idiopathic eruptive macular pigmentation. Case reports . We present 5 cases with chronic, macular grey pigmentation of the skin of the trunk and the limbs. In 2 cases simultaneous appearance of slightly erythematous reaction and itch of the skin were observed. The histopathological picture was similar in all cases. The main features were: incontinentia of the pigment, slight inflammatory infiltrates, and melanophages in the upper dermis. In 2 cases we observed degeneration of the basal cell layer. The course of the diseases was mild. Other laboratory tests were normal. In the majority of cases the cause of the disease was toxic. Conclusions . It seems that discrete differences in histopathological picture and colouring of the lesions are not sufficient to differentiate EDP from ashy dermatosis, lichen planus pigmentosus and idiopathic eruptive macular pigmentation. We believe that all these conditions are forms of the same disease.